Heterogeneity in preferences for renewable home heating systems - Tensay Hadush Meles; Lisa Ryan; Sanghamitra Chattopadhyay Mukherjee (University College Dublin, UCD Centre for Economic Research, 2019)
This paper explores heterogeneity in preferences for renewable home heating, more specifically heat pump systems, using a novel combination of psychological construct statements, based on the theory of planned behavior, and a discrete choice experiment. We employ a latent class analysis of a nationally representative sample of Irish households to identify and characterize distinct respondent classes based on their responses to the statements on attitude, social norm, perceived behavioral control and intention to install heat pump. Furthermore, we conduct a discrete choice experiment with a subsample of randomly selected respondents to estimate preferences for different attributes of a home heating system and the corresponding marginal willingness to pay, where the psychological construct statements are included as explanatory variables. We identify four types of responses to heat pump, revealing different viewpoints towards this technology. Our results show that, in addition to upfront cost and bill savings, non-monetary attributes such as installation hassle and environmental sustainability are important determinants of the uptake of heat pumps. We find that participants' marginal willingness to pay for heat pump attributes is higher in this early stage market for heat pumps than that reported for more established markets. The findings of this study should be useful to policy makers in designing targeted policies to end-user profiles.
Keywords: C25; D91; O33; Q42; 330; Heat Pump Systems; Latent Class Analysis; Choice Experiments; Willingness to Pay; Preference Heterogeneity; Ireland